Pengetahuan Pola Menyikat Gigi Sebelum dan Sesudah Penyuluhan Menggunakan Video Animasi - Septa, Badai; Lesmana, Hans; Sitanaya, Rini; Supriatna, Agus; Wulandari, Nurfadila (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2024)
Dental and oral health are important in the lives of every individual, including children, because damaged and untreated teeth and gums will cause pain, chewing disorders and can affect other body health. Knowledge of oral and dental health in children needs special attention because at this age, children are experiencing the process of growth and development, and the condition of their previous teeth will influence the development of dental health in adulthood. One effort to maintain dental health that is quite effective is through oral health education. The aim of this research is to determine the difference in the level of knowledge of toothbrushing patterns before and after counseling using audiovisual media in the form of animated videos among students at SD Inpres Perumnas. The method in this research uses quantitative research, namely pre-experiment with a One-Group Pretest-Posttest Design, with a population of all SD Inpres Perumnas students. Sampling in this study used the Purposive Sampling method with a sample of 42 students who were class IV students at SD Inpres Perumnas. The data collection instrument used was a questionnaire sheet. The data analysis technique used is the Paired Sample T-test. The research results showed that the average value of knowledge had increased, namely before being given counseling, it was 41.19 and after being given counseling, it was 72.85. Significance (p) is 0.000 which means ≤ (0.05), then Ho is rejected and Ha is accepted. So there is a difference in knowledge of toothbrushing patterns between before and after counseling using audiovisual media in the form of animated videos.